Pemodelan Spasial Genangan Banjir Rob, Studi Kasus: Pesisir Utara Banten (Kecamatan Kasemen) - Dhea Rahma Azhari; Della Ayu Lestari; Willdan Aprizal Arifin (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The northern coast of Banten, especially Kasemen District, is an area with accessibility that is directly opposite the Java Sea and has a sloping topography so that it has vulnerability to the potential for tidal flooding. This certainly has a significant impact on community activities. It is impossible to avoid the risk of tidal flooding, but spatial distribution of land use can be carried out to produce information for policy makers. This study uses a Geographic Information System by utilizing spatial data to analyze tidal flood modeling through historical data scenarios of the worst tidal flood events for the last 3 years, as well as knowing the area of ??vulnerability land with tidal flood detection in the North Coast region of Banten. The spatial approach is carried out through data processing which is divided into several stages, including reassessment, as well as cropping DEMNAS data, rasterization, and carrying out a modeling process to produce a map of the tidal flood area using the equilibrium method. The results showed that the Kasemen District area with a 0.10 meter scenario might inundate an area of ??574.38 ha, a 0.15 meter scenario inundate an area of ??582.67 ha, a 0.20 meter scenario an area of ??591.28 ha, and with a 0.25 meter scenario it inundate an area of 598.49 ha. Keywords: equilibrium, spatial model, tidal flood